Religious Character Development at Pertiwi 2 High School - Tiara Maryanti Putri; Eliza Guspita; Hanifa Fadila; Ridho Efendi; Rafli Asyura; Randi Okta Hidayah; Yovanda Rivaldi; Azvi Rahmi; Serpuadi Zeky (Jurnal Kajian dan Pengembangan Umat, 2026)
This study aims to analyze the role of religious character development in preventing bullying behavior at SMA 2 Pertiwi Padang. This research employed a qualitative approach using the library research method by collecting data from journals, scientific articles, books, and previous studies related to bullying and religious character education. The findings revealed that bullying behavior in schools includes verbal, physical, social, psychological, and cyberbullying, all of which negatively affect students mental, emotional, and social wellbeing. The causes of bullying are influenced by low self-control, weak religious understanding, peer influence, lack of supervision from families and schools, and the rapid development of social media. Religious character development through religious activities, moral habituation, teacher role modeling, and the implementation of a religious school culture has proven effective in improving students empathy, discipline, responsibility, tolerance, and self-control, thereby reducing bullying behavior in schools. In addition, teachers play an important role as educators, mentors, motivators, and role models in creating a safe, comfortable, and harmonious educational environment. Collaboration between schools, families, and communities is also an important factor in supporting the success of sustainable religious character development. Therefore, religious character development can serve as an effective preventive strategy in establishing a bullying-free school culture at SMA 2 Pertiwi Padang and in shaping students with noble character, discipline, and strong social awareness.